Nutrient allocation might affect the cadmium accumulation of Bermuda grass (Cynodon dactylon). (August 2020) - Tan, Shuduan; Liu, Zhongshu; Zeng, Qingru; Zhu, Mingyong; Wang, Andong; Chen, Bin
Abstract: Hydroponic experiments with different cadmium (Cd) concentrations were conducted to explore the impacts of nutrient allocation on the Cd enrichment of Bermuda grass. The results demonstrated with the Cd concentration increase, the accumulation of nitrogen (N), phosphorus (P) and potassium (K) in roots, stems and leaves increased first and then decreased, while the accumulation of Cd had no significant difference. The biomass and N, P and K accumulation of CD1 and CD2 were significantly different from those of CD3 and CD4, but there was no significant difference in Cd accumulation. The root N, P and K distribution ratio of CD4 increased by 47.9%, 114.3% and 64.3% compared with those of CD2 treatment, the values of stem decreased by 29.4%, 22.4% and 17.2%, and the values of leaves increased by 15.8%, 19.8% and 23.6% respectively. The K ratio of root and leaf increased and that of stem decreased. Cd reduced N and K distribution ratio of stem and increased N and K distribution ratio of root and leaf. Pearson correlation analysis showed that the accumulation of N, P and K in stems was positively correlated with the accumulation of Cd in stems, and the accumulation of N, P and K in roots, stems and leaves were positively correlated with the Cd accumulation in leaves. Bermuda grass can schedule the nutrient allocation to adapt to the Cd absorption and enrichment in different organs under different Cd concentrations. In conclusion, nutrient allocation might affect the Cd accumulation of Bermuda grass. Highlights: The nutrient distribution of plants is related to the Cd accumulation. Bermuda grass can adjust the nutrient allocation under different Cd concentrations. Nutrient allocation might affect the Cd accumulation of Bermuda grass.